Relation between explant age, total phenols and regeneration response in tissue cultured cotton (Gossypium hirsutum L.) - (:unkn) unknown (ACADEMIC JOURNALS, 2007)
The aim of this study is to determine total phenol amount of the explants and to expose relation between explant age, total phenols and regeneration response for tissue culture and gene transfer systems of cotton (Gossypium hirsutum L.). In this study, total phenol amount of 7, 14, 21 and 28 day old cotton (G. hirsutum L) var. Nazilli 84S explants and excreted total phenols into culture media were determined during the germination period. Explants were originated from roots, hypocotyls, cotyledons and leaves. After germination, they were cultured on Murashige and Skoog (MS) media, supplemented with 0.1 mg/L kinetin (KIN) and grown at 25 degrees C under fluorescent light (7500 lux), 16 h light and 8 h dark for 3 weeks. Different regeneration ratios were obtained relative to explant age and total phenol amounts. Regenerated shoots were rooted on woody plant medium (WPM) supplemented with 1 mg/L indole-3-butyric acid (IBA).
Keywords: Gossypium hirsutum L.; tissue culture; germination; total phenol; browning; PEROXIDASE; CELLS